THE EFFECT OF PEER TUTOR EMPOWERMENT WITH THE METHOD THINK PAIR SHARE (TPS) ON KNOWLEDGE AND ATTITUDE OF ADOLESCENTS ABOUT MENTAL HEALTH IN STATE JUNIOR HIGH SCHOOL 5 BENGKULU CITY - Linda Sitompul; Mutia Asnimulia; Darwis (Poltekkes Kemenkes Bengkulu, 2023)
Mental health issues can be strike by anyone, including children and adolescents. The high number of mental health disorders in adolescents in Bengkulu City requires preventive action. Efforts that can be made are providing health education about mental health to adolescents in the form of empowering peer tutors using the Think Pair Share Method. This study aims to determine the effect of empowering peer tutors using the TPS method on adolescents' knowledge and attitudes about mental health. This research is a quantitative research with a quasi-experimental research design with a one group pretest-posttest design. The population in this study were students of class 8th SMP Negeri 5 Bengkulu City and used a simple random sampling technique to get a total of 40 respondents. Data analysis used on test is the Wilcoxon test.The results of the implementation of peer tutor empowerment using the TPS method obtained an average observation of tutor activity and promoter activity of 96.93% with a very good category. In TPS activities, almost all groups participated actively with an average of 86.17 in the very good category. The mean knowledge of adolescents increased by 92.06 in the very good category. The mean attitude increased by 86.50 in the very good category. Calculation of the test on knowledge and attitude variables through the Wicoxon test obtained Sig. <0.05, which means that there is an effect of empowering peer tutors using the TPS method on the knowledge and attitudes of adolescents about mental health at SMP Negeri 5 Bengkulu City.